Glacier–plume or glacier–fjord circulation models? A 2-D comparison for Hansbreen–Hansbukta system, Svalbard. Issue 265 (5th October 2021) - De Andrés, Eva; Otero, Jaime; Navarro, Francisco J.; Walczowski, Waldemar
Abstract: Up to 30% of the current tidewater mass loss in Svalbard corresponds to frontal ablation through submarine melting and calving. We developed two-dimensional (2-D) glacier–line–plume and glacier–fjord circulation coupled models, both including subglacial discharge, submarine melting and iceberg calving, to simulate Hansbreen–Hansbukta system, SW Svalbard. We ran both models for 20 weeks, throughout April–August 2010, using different scenarios of subglacial discharge and crevasse water depth. Both models showed large seasonal variations of submarine melting in response to transient fjord temperatures and subglacial discharges. Subglacial discharge intensity and crevasse water depth influenced calving rates. Using the best-fit configuration for both parameters our two coupled models predicted observed front positions reasonably well (±10 m). Although the two models showed different melt-undercutting front shapes, which affected the net-stress fields near the glacier front, no significant effects on the simulated glacier front positions were found. Cumulative calving (91 and 94 m) and submarine melting (108 and 118 m) along the simulated period showed in both models (glacier–plume and glacier–fjord) a 1:1.2 ratio of linear frontal ablation between the two mechanisms. Overall, both models performed well on predicting observed front positions when best-fit subglacial discharges were imposed, the glacier–plume model being 50 times computationally faster.